2021
DOI: 10.1007/s40544-021-0499-z
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of co-textured cylinder liner-piston ring during running-in

Abstract: The running-in of cylinder liner-piston rings (CLPRs) is the most important process that must be performed before a marine diesel engine can be operated. The quality of running-in directly affects the reliability of a CLPR. The surface texture of a CLPR has been proven to significantly affect its lubrication performance. In this study, the tribological behavior of a CLPR during running-in is investigated. Three types of surface textures are generated on the CLPR via laser processing: dimple texture on piston r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, additional surface texturing of the cylinder liner is seldom performed in the motorized industry, because of the increasing cost. Combining the texturing of the piston ring and the cylinder liner is another possibility [ 27 ], however, the cost of machining would be seriously increased. Most likely only high-performance engines have the potential be designed with oil pockets on the cylinder surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, additional surface texturing of the cylinder liner is seldom performed in the motorized industry, because of the increasing cost. Combining the texturing of the piston ring and the cylinder liner is another possibility [ 27 ], however, the cost of machining would be seriously increased. Most likely only high-performance engines have the potential be designed with oil pockets on the cylinder surface.…”
Section: Discussionmentioning
confidence: 99%
“…Miao et al [ 27 ] compared the effects of the piston ring and the cylinder liner texturing on the tribological performance of the piston ring assembly. The surface of the cylindrical liner contained grooves, while the piston ring contained isolated circular dimples.…”
Section: Functional Performance Of Textured Cylinder Liner Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…While surface texturing has been applied to cylinder walls of internal combustion engines [59,60] or on both the liner and piston rings [61], this paper focuses on the laser surface texturing of piston rings.…”
Section: Tribological Test With Laser Textured Piston Ringcylinder Li...mentioning
confidence: 99%
“…Tang et al [ 38 ] redesigned the crescentiform surface texture and investigated the tribological properties of ethylene propylene diene monomer (EPDM) rubber under different loading conditions, and the results showed that under low loading conditions, the crescentiform surface texture can effectively reduce the friction coefficient of the friction pair and reduce corrosive wear and adhesive wear. Miao et al [ 39 , 40 ] compared the friction performance of cylinder liner and piston ring (metal–metal seal) with single texture and coupling texture. Compared with single texture, the friction performance of coupling texture is better; the surface of the texture is easier to generate a stable oil film, which can enhance the ability to collect abrasive chips to prevent abrasive chips from scratching the surface and play a role in reducing friction.…”
Section: Introductionmentioning
confidence: 99%